Why Re-open the Debate on the Preliminary Inquiry? Some Preliminary Empirical Observations - Webster, Cheryl Marie; Bebbington, Howard H. (Canadian Journal of Criminology and Criminal Justice, 2013)
The preliminary inquiry has existed as a procedural protection in our criminal justice system for well over a century. Despite its longevity, this procedural option has not been without controversy. Particularly over the last several decades, there has been considerable debate surrounding its continuing value. Recently, a 2012 press release by the federal, provincial, and territorial ministers responsible for justice and public safety suggests that reform (and quite possibly abolition) of the preliminary inquiry is again being considered. The present article provides an empirical context in which to think about preliminary inquiry reform. Using a detailed and comprehensive national data set, developed in 2003 and specifically tailored to examine this criminal procedure, we do not find a clear case for re-opening the debate. The preliminary inquiry appears to have value in reducing the use of expensive court resources, either by altering the course of cases destined for Superior Court or by eliminating weak charges. Its costs in terms of court delay and valuable resources are significantly limited by its infrequent use and few court appearances. At a minimum, this article suggests that a more detailed empirical examination is justified (if not required) before any changes are made to the preliminary inquiry.